Single-Stage Open Repair of Extensive Arch and Descending Thoracic Aneurysm through Sternotomy: A Case Report - Joon Young Kim (Korean Society for Thoracic & Cardiovascular Surgery, 2021)
Extensive thoracic aortic disease involving the ascending aorta, the aortic arch, and the descending thoracic aorta may require multiple surgical and interventional managements, which impose a burden in terms of cumulative surgical trauma and the risk of interval mortality. Herein, we describe a single-stage arch and descending thoracic aorta replacement via sternotomy in a patient with multiple comorbidities presenting with an extensive thoracic aortic aneurysm.